Natural Killer Cell Immunomodulation: Targeting Activating, Inhibitory, and Co-stimulatory Receptor Signaling for Cancer Immunotherapy - Chester, Cariad; Fritsch, Katherine; Kohrt, Holbrook E. (Frontiers in Immunology, 2015)
There is compelling clinical and experimental evidence to suggest natural killer (NK) cells play a critical role in the recognition and eradication of tumors. Efforts at using NK cells as antitumor agents began over two decades ago, but recent advances in elucidating NK cell biology have accelerated the development of NK cell-targeting therapeutics. NK cell activation and the triggering of effector functions is governed by a complex set of activating and inhibitory receptors. In the early phases of cancer immune surveillance, NK cells directly identify and lyse cancer cells. Nascent transformed cells elicit NK cell activation and are eliminated. However, as tumors progress, cancerous cells develop immunosuppressive mechanisms that circumvent NK cell-mediated killing, allowing for tumor escape and proliferation. Therapeutic intervention aims to reverse tumor-induced NK cell suppression and sustain NK cells’ tumorlytic capacities. Here, we review tumor-NK cell interactions, discuss the mechanisms by which NK cells generate an antitumor immune response, and discuss NK cell-based therapeutic strategies targeting activating, inhibitory, and costimulatory receptors.